The Role of Retinal Pigment Epithelial Cells in Regulation of Macrophages/Microglial Cells in Retinal Immunobiology - Taylor, Andrew W.; Hsu, Samuel; Ng, Tat Fong (Frontiers in Immunology, 2021)
The ocular tissue microenvironment is immune privileged and uses several mechanisms of immunosuppression to prevent the induction of inflammation. Besides being a blood-barrier and source of photoreceptor nutrients, the retinal pigment epithelial cells (RPE) regulate the activity of immune cells within the retina. These mechanisms involve the expression of immunomodulating molecules that make macrophages and microglial cells suppress inflammation and promote immune tolerance. The RPE have an important role in ocular immune privilege to regulate the behavior of immune cells within the retina. Reviewed is the current understanding of how RPE mediate this regulation and the changes seen under pathological conditions.